Effects of Bengkoang (Pachyrhizus erosus (L) Urb Juice in Hampering Blood Glucose in Rat Models - Adrian Dwiputra Widyarman; Emma Nurdiamah; Nanny Natalia Muliani Soetedjo (Althea Medical Journal, 2014)
Background : The prevalence of diabetes mellitus in Indonesia tends to increase and is predicted to reach 21.3 millions in 2030. Bengkoang (Pachyrhizus erosus (L) Urb. is one of the traditional medicine frequently used in diabetes treatment.The objective of this study is to assess the effectiveness of bengkoang juice in hampering blood glucose increase.Methods : Fourty alloxan-induced diabetic Wistar rats were used in this study. After 16 hours of fasting, the blood glucose was measured using glucometer EasyTouch Blood Glucose/Cholesterol/Uric Acid Multi-Function Monitoring System. The positive control group was given 7 ml of distilled water and 50% glucose solution with 2.5 g/kg dosage while the study group were given 7 ml of bengkoang juice and 50% glucose solution with 2.5 g/kg dosage. Blood glucose was re-checked after 2 hours. This procedure was performed in October 2012.The results were analyzed using Student’s T-test with α = 0.05.Results: The result shows a significant difference in blood glucose increase between the control and study groups with a score of 121.11 mg/dL and 324.45 mg/dL respectively. This result shows that bengkoang juice increases blood glucose level in Wistar rats.Conclusions: In conclusion, bengkoang (Pachyrhizus erosus (L) Urb. juice has no effect in hampering the blood glucose level increase in Wistar rats. [AMJ.2014;1(1):25–9]Keywords: Alloxan, blood glucose, diabetes mellitus, Pachyrhizus erosus (L) Urb. Pengaruh Bengkoang (Pachyrhizus erosus (L) Urb Juice dalam Menghambat Glukosa Darah pada TikusLatar Belakang: Prevalensi diabetes mellitus di Indonesia cenderung meningkat dan diperkirakan mencapai 21,3 juta pada tahun 2030. Bengkoang (Pachyrhizus erosus ( L ) Urb adalah salah satu obat tradisional yang sering digunakan untuk pengobatan diabetes. Tujuan penelitian ini adalah untuk menilai efektivitas jus bengkoang dalam menghambat peningkatan glukosa darah.Metode: Empat puluh tikus Wistar yang telah diinduksi diabetes aloksan digunakan dalam penelitian ini. Setelah 16 jam puasa, glukosa darah diukur dengan menggunakan glucometer Glukosa Darah EasyTouch / Kolesterol / Asam Urat Monitoring System Multi- Function . Kelompok kontrol positif diberi 7 ml air suling dan larutan glukosa 50 % dengan 2,5 g / kg dosis sedangkan kelompok studi diberi 7 ml jus bengkoang dan larutan glukosa 50 % dengan 2,5 g / kg dosis . Glukosa darah diperiksa kembali setelah 2 jam. Prosedur ini dilakukan pada hasil Oktober 2012 dianalisis menggunakan T -test Student dengan α = 0,05.Hasil: Hasil penelitian menunjukkan perbedaan yang signifikan dalam peningkatan glukosa darah antara kelompok kontrol dan kelompok studi dengan skor 121.11 mg / dL dan 324,45 mg / dL masing-masing . Hasil ini menunjukkan bahwa jus bengkoang meningkatkan kadar glukosa darah pada tikus Wistar .Simpulan: Bengkoang ( Pachyrhizus erosus ( L ) Urb jus tidak berpengaruh dalam menghambat kenaikan kadar glukosa darah pada tikus Wistar .Kata kunci: Aloksan , glukosa darah , diabetes mellitus , Pachyrhizus erosus ( L ) Urb. DOI: 10.15850/amj.v1n1.293